Atmospheric Corrosion of Copper Exposed in a Simulated Coastal-Industrial Atmosphere. Issue 6 (June 2017) - Pan, Chen; Lv, Wangyan; Wang, Zhenyao; Su, Wei; Wang, Chuan; Liu, Shinian
Abstract : The corrosion behavior of copper exposed in a simulated coastal-industrial atmosphere has been investigated using weight loss measurement, scanning electron microscopy, X-ray diffraction, potentiodynamic polarization and in-situ electrochemical impedance spectroscopy (EIS) with micro-distance electrodes. The results show that corrosion kinetics follows the empirical equation D = At n . The main corrosion products are composed of Cu2 O, Cu2 Cl(OH)3 and Cu4 Cl2 (OH)6 . A two-layer structure comprising a loose outer layer and a compact inner layer forms the corrosion products during corrosion process. SO2 has been found to promote the formation of Cu4 Cl2 (OH)6 .